The dung beetles (Coleoptera: Scarabaeidae: Scarabaeinae) from Oglán Alto Protective Forest, Pastaza, Ecuador - William R. Chamorro; Freddy O. Gallo; Soraya Delgado; Sandra I. Enríquez; Verónica Guasumba; Germán López-Iborra (Biota Colombiana, 2019)
The Oglán Alto Protective Forest has an area of 3100 hectares and is dominated by Amazonian lowland and piedmont forests, which harbor great diversity of fauna and flora. However, such diversity has been poorly studied, especially insects. Here we present an inventory of the dung beetles (Coleoptera: Scarabaeidae: Scarabaeinae) for this locality. A total of 10,627 individuals, belonging to 17 genera and 65 species, were determined during 18 months of collection, in which 11 different sampling methods were used. This research presents and updated checklist and a photographic guide of the main genera and species of dung beetles identified in the study area.